2017
DOI: 10.1016/j.repc.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Severe thrombocytopenia induced by iodinated contrast after coronary angiography: The use of gadolinium contrast and intravascular ultrasound as an alternative to guide percutaneous coronary intervention

Abstract: Acute contrast-induced thrombocytopenia is a rare event with the use of modern low osmolarity iodinated contrast media. The pathophysiological mechanism that causes platelet counts to drop has not been identified, but an immunological mechanism is suspected due to cytotoxicity after previous exposure to contrast. We report the case of a 47-year-old male patient with acute severe thrombocytopenia due to iodinated contrast media exposure. His platelet count after the procedure with the highest amount of contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…While the underlying mechanisms are still to be clarified, mechanical platelet destruction could occur after the administration of hypo-osmolar iodinated contrast agents [ 18 ]. Several papers [ 6 , 8 , 19 ] described BEV patients as more vulnerable to PR because the delivery procedures typically required a large number of low-osmolar contrast agents to confirm appropriate valve positioning. However, this hypothesis was never confirmed by solid evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the underlying mechanisms are still to be clarified, mechanical platelet destruction could occur after the administration of hypo-osmolar iodinated contrast agents [ 18 ]. Several papers [ 6 , 8 , 19 ] described BEV patients as more vulnerable to PR because the delivery procedures typically required a large number of low-osmolar contrast agents to confirm appropriate valve positioning. However, this hypothesis was never confirmed by solid evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez-Enriquez and coauthors described a high rate of life-threatening bleeding events, major vascular complications, a greater need for RBC transfusions, and a high rate of sepsis and mortality in patients with a platelet count decrease over 30% at a 30-day follow-up [ 7 ]. Furthermore, Dvir and colleagues also reported prolonged ICU LoS and acute kidney injury as the drawbacks related to thrombocytopenia in TAVI patients [ 19 ]. Abu Khadija and associates reported that post-procedural PR was associated with higher rates of major bleeding, vascular complications, and mortality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracoronary diagnostic techniques, such as intravascular ultrasound (IVUS), play an important role in complementing coronary intervention, solving the limitations of gadolinium. Our group presented the first published case of IVUS-guided percutaneous coronary intervention (PCI) using gadolinium as a contrast medium [8].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous contrast media can also induce acute thrombocytopenia, although it is a very rare complication that has been mostly reported in patients who received ionic contrast media, which was usually used for coronary arteriography. 1 2 3 Non-ionic contrast-induced acute thrombocytopenia is far more rare and has been usually accompanied by signs or symptoms of immediate allergic reaction, including respiratory distress, chest discomfort, facial flushing, or skin rash. 4 5 …”
Section: Introductionmentioning
confidence: 99%